2018
DOI: 10.1002/met.1735
|View full text |Cite
|
Sign up to set email alerts
|

Global Positioning System precipitable water vapour (GPS‐PWV) jumps before intense rain events: A potential application to nowcasting

Abstract: A rapid increase in atmospheric water vapour is a fundamental ingredient for many intense rainfall events. High‐frequency precipitable water vapour (PWV) estimates (1 min) from a Global Positioning System (GPS) meteorological site are evaluated in this paper for intense rainfall events during the CHUVA Vale field campaign in Brazil (November and December 2011) in which precipitation events of differing intensities and spatial dimensions, as observed by an X‐band radar, were explored. A sharp increase in the GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 50 publications
(74 reference statements)
2
24
1
3
Order By: Relevance
“…Figure 11 shows the time series of 3-min PWVs over the HKLT station and hourly precipitation at the precipitation station (co-located with the HKLT station, see Figure 1) depicted in the histogram during the four-day period of 15-18 September. Several studies have shown that precipitation occurred either when PWV reaches its peak or in the initial period after a sharp decrease [39,44,45]. However, typhoons provide abundant moisture, which is likely to cause precipitation events and accelerate the formation of saturated states of water in the region covered by typhoons.…”
Section: Relationship Between Variations In Pwv and Atmospheric Parammentioning
confidence: 99%
“…Figure 11 shows the time series of 3-min PWVs over the HKLT station and hourly precipitation at the precipitation station (co-located with the HKLT station, see Figure 1) depicted in the histogram during the four-day period of 15-18 September. Several studies have shown that precipitation occurred either when PWV reaches its peak or in the initial period after a sharp decrease [39,44,45]. However, typhoons provide abundant moisture, which is likely to cause precipitation events and accelerate the formation of saturated states of water in the region covered by typhoons.…”
Section: Relationship Between Variations In Pwv and Atmospheric Parammentioning
confidence: 99%
“…This delay, known as the Zenith Total Delay, can be separated into a wet (PWV driven) and dry (non-PWV) component through the use of atmospheric models (Tralli & Lichten 1990). Although this approach is a recent advent in astronomy (Braun & Hove 2005;Dumont & Zabransky 2001;Nahmias & Zabransky 2004;Blake & Shaw 2011), the use of GPS to measure PWV has a longer history in meteorology (Bevis et al 1992) and has undergone continual improvement with a focus on minimizing the estimated uncertainty, often achieving levels 2 mm (Moore et al 2015;Shangguan et al 2015;Sapucci et al 2019).…”
Section: Precipitable Water Vapormentioning
confidence: 99%
“…By analyzing the temporal variations in PWV time series over the Arabian Sea and the Bay of Bengal, Singh et al [45] concluded that the relatively higher PWV (around 70−90 mm) during the months of May and June is closely correlated with the onset of south-west monsoon. In addition, considerable increases in GPS-PWV (over 9.5 mm/h) before the heavy precipitation events happened in Brazil were found and regarded as "GPS-PWV jumps" by Sapucci et al [46], which are likely to be strongly linked to water vapor convergence and the continued formation of cloud droplets and raindrops. Zhang et al [47] also stated that PWV could be used to complement conventional meteorological observations for the monitoring and predictions of severe weather events.…”
Section: Introductionmentioning
confidence: 99%